547-32.54-057:543.33 Kimyo va kimyoviy texnologiyalar: SEM ANALYSIS AND THERMAL PROPERTIES OF SYNTHESISED SORBENT BASED ON UREA, FORMALDEHYDE, CITRIC ACID - Mukumova, Gulvar; Turaev, Khayit; Kasimov, Sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Objective. Goal. Worldwide, wastewater is characterized by pollution, a great danger to the environment and all forms of life.Therefore, before draining contaminated water, it must be properly treated to mitigate its harmful effects. This work studied the thermal analysis of the sorbent obtained for wastewater treatment on the basis of urea, formalin and citric acid, as well as the complex compound formed by it with heavy metals contained in wastewater. Methods. The article presents an analysis of differential thermal analysis (DTA) and thermogravimetric (TG) analyses of urea, formalin, and citric acid-based sorbents. The results of the curve from the differential thermal analysis (DTA) and thermogravimetric (TG) representation of the synthesized sorbent have been analyzed. The process of thermal decomposition is a complex stage of many stages, which goes away with the release of intermediate products. The thermal decomposition of sorbent complexes with certain metal ions is also significantly influenced by the presence of a metal and the components of complex compounds. . Results. The thermal decomposition of sorbent complexes with certain metal ions is also significantly influenced by the presence of a metal and the components of complex compounds. Thermal analysis of the complex formed by kfl-sorbenting Zn(II) has been studied. Conclusion. Thermal analysis of the complex formed by sorbenting Zn(II), obtained on the basis of urea, formalin, and citric acid, has been studied. Based on the analysis of the results, it was concluded that compounds such as H2O, NH3 CO, and CO2 are formed from different functional groups during the degradation of sorbent obtained on the basis of urea, formalin, and citric acid. An analysis of the polyfunctional complex-forming sorbent in a scanning electron microscope is given.